2010
DOI: 10.1111/j.1399-0012.2010.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Taking immunosuppressive medications effectively (TIMELink): a pilot randomized controlled trial in adult kidney transplant recipients

Abstract: Background-Immunosuppressive medication non-adherence is one of the most prevalent but preventable causes of poor outcomes in adult renal transplant recipients, yet there is a paucity of studies testing interventions in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
90
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 28 publications
(46 reference statements)
1
90
0
4
Order By: Relevance
“…Therefore, effective, evidence-based intervention strategies are needed to promote long-term IST adherence in RTRs, which in turn results in improved graft survival and may impact other outcomes such as decreased healthcare utilizations and costs. However, previous studies of interventions targeting IST adherence among adult RTRs have produced inconsistent results and have not assessed outcomes linked to adherence such as healthcare utilizations and costs (6)(7)(8)(9). The current RCT is the first study to address this gap in the knowledge base through examination of the effects of a behavioral contract intervention on IST adherence and healthcare utilizations in an adult RTR sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, effective, evidence-based intervention strategies are needed to promote long-term IST adherence in RTRs, which in turn results in improved graft survival and may impact other outcomes such as decreased healthcare utilizations and costs. However, previous studies of interventions targeting IST adherence among adult RTRs have produced inconsistent results and have not assessed outcomes linked to adherence such as healthcare utilizations and costs (6)(7)(8)(9). The current RCT is the first study to address this gap in the knowledge base through examination of the effects of a behavioral contract intervention on IST adherence and healthcare utilizations in an adult RTR sample.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies are hampered by ineffective interventions and/or lack of examination of outcomes related to adherence such as healthcare utilizations and costs, which were found to be associated with decreased IST adherence levels in a retrospective cohort study by Pinsky et al (2,(6)(7)(8)(9). Given the limits of prior published interventional studies, prospective research is needed to evaluate the effects of interventions on IST adherence and healthcare outcomes among adult RTRs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since sample size affects studies' statistical power, the effect intervention studies that are not fully powered may not be adequately tested or realized [32] . Though the study by Russell et al (2010) was not powered to detect a difference between groups, the study did find a statistically significant difference between the groups, which supports the large effect size of the CSI personal improvement intervention. The study by Matteson et al (2011) had a small sample size and was not adequately powered to find a statistically significant difference; however, the study found a large effect size.…”
Section: Discussionmentioning
confidence: 56%
“…Russell et al (2010) found the CSI intervention was effective immediately, which indicates that providers may be able to deliver it brief patient encounters. Matteson et al (2011) found with a single dose of CSI delivered in the clinical setting had a very large effect size.…”
Section: Discussionmentioning
confidence: 99%